A series of two‐dimensional lanthanide coordination polymers: synthesis, structures, magnetism and selective luminescence detection for heavy metal ions and toxic solvents. Issue 2 (31st January 2019) - Hao, Hongguo; Liu, Hongyan; Wang, Yuchen; Yuan, Suxian; Xu, Han; Zhang, Jingyue; Wang, Ying; Li, Dacheng; Sun, Junshan
Abstract : A series of two‐dimensional (2D) coordination polymers has been synthesized from rigid biphenyl‐3, 3′, 5, 5′‐tetracarboxylic acid under solvothermal conditions. The four compounds are isomorphous and feature similar 2D double layers, which are further extended via interlayer hydrogen‐bonding interactions into three‐dimensional supramolecular structures. Abstract : A series of two‐dimensional (2D) coordination polymers (CPs), namely poly[[bis(μ‐acetato)diaqua(μ6 ‐biphenyl‐3, 3′, 5, 5′‐tetracarboxylato)bis( N, N ‐dimethylacetamide)digadolinium(III)] N, N ‐dimethylacetamide monosolvate], [Gd2 (C16 H6 O8 )(C2 H3 O2 )2 (C4 H9 NO)2 (H2 O)2 ]·C4 H9 NO n (CP1 ), poly[[bis(μ‐acetato)diaqua(μ6 ‐biphenyl‐3, 3′, 5, 5′‐tetracarboxylato)bis( N, N ‐dimethylacetamide)didysprosium(III)] N, N ‐dimethylacetamide monosolvate], [Dy2 (C16 H6 O8 )(C2 H3 O2 )2 (C4 H9 NO)2 (H2 O)2 ]·C4 H9 NO n (CP2 ), poly[bis(μ‐acetato)diaqua(μ6 ‐biphenyl‐3, 3′, 5, 5′‐tetracarboxylato)bis( N, N ‐dimethylacetamide)dineodymium(III)], [Nd2 (C16 H6 O8 )(C2 H3 O2 )2 (C4 H9 NO)2 (H2 O)2 ] n (CP3 ), poly[bis(μ‐acetato)diaqua(μ6 ‐biphenyl‐3, 3′, 5, 5′‐tetracarboxylato)bis( N, N ‐dimethylacetamide)disamarium(III)], [Sm2 (C16 H6 O8 )(C2 H3 O2 )2 (C4 H9 NO)2 (H2 O)2 ] n (CP4 ), has been synthesized from rigid biphenyl‐3, 3′, 5, 5′‐tetracarboxylic acid under solvothermal conditions. Their structures have been determined by single‐crystal X‐ray diffraction analyses, elemental analyses, IR spectra, powder X‐ray diffraction and thermogravimetric analyses, andCP1 –CP4 crystallize in the monoclinic space group P 21 / n .CP1 –CP4 are isomorphous and feature similar 2D double layers, which are further extended via interlayer hydrogen‐bonding interactions into a three‐dimensional (3D) supramolecular structure. Hydrogen‐bonding interactions between N, N ‐dimethylacetamide molecules and carboxylate O atoms strengthen the packing of the layers. The organic ligands interconnect with metal ions to generate 2D layered structures with a (4, 4)‐connected net having 4 4 .6 2 topology.CP1 has been investigated for its magnetic properties and magnetic susceptibility measurements were carried out in the range 2.0–300 K. The results of the magnetic measurements show weak antiferromagnetic coupling between the Gd III ions inCP1 . Moreover, the strong luminescence ofCP2 andCP4 can be selectively quenched by the Fe 3+ ion and toxic solvents ( e.g. acetone).